EFFECTS OF SORGHUMS BASED FEED ON BROILER CHICKENS WEIGHT GAIN FOR AGRIBUSINESS IN BAUCHI STATE, NIGERIA - ADAMU I.; ISHAQB.A.; CHIROMA D. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The study investigated the effects of sorghums feed on broiler chickens weight gain and carcass quality for agribusiness in Bauchi state, Nigeria. Experimental research design was adopted for the study using one hundred broilers chickens. The chickens were grouped into four and feed with different source of energy feed (Maize, White Sorghum, Red Sorghum and Yellow Sorghum) but with similar treatments. At the end of the experiment, four broilers were randomly selected from each starved for 12 hours from each group, weighed and slaughtered for carcass evaluation. The weighed of edible parts was recorded for carcass quality. The data collected were analyzed using mean score for research questions while ANOVA was employed to test the null hypotheses at the 0.05 level of significance. The study revealed that the no significant difference among the average weight gains, carcass quality, average total cost and profits of broiler chickens fed with maize, red sorghum, yellow sorghum and white sorghum. It was concluded that replacing the use of sorghum-based as source of energy of broilers chickens with improve the profitability of the business. The study recommended that Sorghum feeds should be used as a replacement of maize for broiler chicken agri-business in Bauchi state